2
$\begingroup$

I've found another thread with a similar question, but none of the answers help with the specific part I'm stuck on.

Just to make things simpler, I've used the square of the distance $f(x_1,x_2,y_1,y_2)=(x_1-x_2)^2+(y_1-y_2)^2$, and I have constraints $G_1=x_1^2-y_1$, and $G_2=x_2-y_2-1$.

Taking the gradients of $f$, $G_1$, and $G_2$, I have the system of equations

$2(x_1-x_2)=2\lambda_1x_1$

$2(y_1-y_2)=-\lambda_1$

$-2(x_1-x_2)=\lambda_2$

$-2(y_1-y_2)=-\lambda_2$

What I've done so far is, I've first observed that the immediate implication of the 2nd and 4th equations is that $\lambda_1=-\lambda_2$. Using this, I cancelled out the 1st and 3rd equations with the substituted value for $\lambda_2$, and got that $2\lambda_1x_1=\lambda_1\implies x_1=\frac{1}{2}$, and by constraint 1 that $y_1=\frac{1}{4}$. From here though, I'm not sure how to pin down the value of $\lambda$, and therefore determine $x_2$ and $y_2$.

$\endgroup$
  • 1
    $\begingroup$ From equation 1 you obtain $x_2 =(1-\lambda_1)/2$, from equation 2 you obtain $y_2= (1+2 \lambda_1)/4$. Using the constraint $G_2$, you obtain $\lambda_1 = -3/4$ and with that the remaining values. $\endgroup$ – Fabian Jan 20 '17 at 9:18
2
$\begingroup$

The shortest distance between the parabola $y = x^2$ and straight line $y = x - 1$ occurs when the tangent to the parabola is parallel to the line, i.e. when their slopes are equal. Now, slope of tangent of parabola $y = x^2$ is

$$ m = \frac{dy}{dx} = 2x $$

and the slope of the straight line $= 1$. Hence the shortest distance occurs at $x = 1/2$. The point on the parabola corresponding to $x = 1/2$ is $(1/2, 1/4)$. Hence, perpendicular distance of this point from the given straight line is:

$$ d = \frac{|0.5 - 0.25 - 1|}{\sqrt{2}} = \frac{3}{4\sqrt{2}} $$

which is the shortest distance between the curves.

EDIT: This, I guess, isn't the answer you're looking for. But I find this approach much easier and shorter than using Lagrange multipliers. Hence just shared this technique.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Yeah, normally this would've been the technique I would've used, given how intuitive its approach is. I'm specifically preparing for a test involving Lagrange multipliers though, which is why I'm using an otherwise overkill method. $\endgroup$ – George Jan 20 '17 at 8:00
1
$\begingroup$

the distance between the curves is given by $$\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}$$ with $$y_1=x_1^2,y_2=x_2-1$$ with these equations we obtain $$\sqrt{(x_2-x_1)^2+(x_2-1-x_1^2)^2}$$ now you must differentiate this with respect to $$x_1,x_2$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ What do I use as the constraints for the Lagrange multiplier in this case? $\endgroup$ – George Jan 20 '17 at 7:55
0
$\begingroup$

Perhaps one could use Lagrange multipliers in more elegant way, but this will work.

Define $$D(x,y,x',y') = (x-x')^2+(y-y')^2$$ and $$g(x,y,x',y') = (y-x^2)^2 + (y'-x'+1)^2.$$

Then you want to optimize $D$ with respect to $g(x,y,x',y') = 0$. Calculate gradients:

$$\nabla D = 2(x-x',y-y',-(x-x'),-(y-y'))\\ \nabla g = 2((y-x^2)(-2x),y-x^2,-(y'-x'+1),y'-x'+1)$$

Set $\nabla D = \lambda \nabla g$ to get system

\begin{align} x-x' &=-2\lambda x(y-x^2)\\ y-y' &=\lambda (y-x^2)\\ x-x' &=\lambda (y'-x'+1)\\ y-y' &=-\lambda (y'-x'+1)\\ \end{align}

From equations 1 and 2 we get $$x-x' = -2x(y-y')$$ and from equations 3 and 4 we get $$x-x' = -(y-y')$$ which gives us $$(2x-1)(y-y') = 0$$ You can quickly check that $y-y' = 0$ is impossible since it would imply that $x-x'= 0$ as well, but our parabola and line do not intersect. Thus, $x = \frac 12$. Now you know $y = \frac 14$ and from the system \begin{align}x-x' &= y'-y\\ y' &= x'-1\end{align} you can get $x'$ and $y'$. This will give you your distance.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.